Quantitative proteomics and biological activity of extracellular vesicles engineered to express SARS‐CoV‐2 spike protein. Issue 10 (13th October 2022) - Choi, Dongsic; Khan, Nargis; Montermini, Laura; Tawil, Nadim; Meehan, Brian; Kim, Dae‐Kyum; Roth, Frederick P.; Divangahi, Maziar; Rak, Janusz
Abstract: SARS‐CoV‐2 viral infection led to the devastating COVID‐19 pandemic, where illness stemmed from interactions between virions and recipient host cells resulting in multi‐layered pathological consequences. The role of the infection portal is now understood to be the cellular angiotensin converting enzyme‐2 (ACE2) receptor, which binds to viral spike (S) protein initiating virion internalisation process. Since SARS‐CoV‐2 virions bear some resemblance to endogenously produced small extracellular vesicles (sEVs) we reasoned that EVs engineered to express S protein (viral mimics) may interfere with viral infection. Here, we report generation of HEK293T cells producing sEVs enriched for transmembrane S‐protein tagged with green fluorescent protein (S/GFP). Strikingly, S protein drove the GFP tag to the membrane of sEVs, while GFP alone was not efficiently included in the sEV cargo. High‐throughput quantitative proteomics revealed that S/GFP sEVs contained over 1000 proteins including canonical components of the exosomal pathway such as ALIX, syntenin‐1, and tetraspanins (CD81, CD9), but depleted for calnexin and cytochrome c. We found that 84 sEV proteins were significantly altered by the presence of S/GFP. S protein expressing EVs efficiently adhered to target cells in an ACE2‐dependent manner, but they were poorly internalised. Importantly, prolonged administration of S/GFP EV to K18‐hACE2 mice provided a significant protection against SARS‐CoV‐2 infection. Thus, the generation of sEV containing S protein can be considered as a novel therapeutic approach in reducing the transmission of SARS‐CoV‐2.